EKSPLORASI SPATIAL DAN IDENTIFIKASI CENDAWAN ENDOFIT PADA TANAMAN KAKAO (Theobroma cacao L.) DI BALI - Lilis Riana Tambunan; Meitini Proborini; Putu Adriani Astiti (Simbiosis: Journal of Biological Sciences, 2018)
Cocoa plant (Theobroma cacao L.) can grow well in the highlands and lowlands, a plantation and industrial plant which is known as one of the export commodities, as raw material for the food and pharmaceutical industries which can contribute to an increase in foreign exchange endophytic fungus is a fungus living on a live network of plants such as seeds, leaves, flowers, twigs, stems and roots. Truffles are generally mutualistic endophyte and is known to stimulate the growth of plants, capable of producing antibiotics and plant growth regulators (hormones). This study aims to determine the diversity and identify endophytic fungi on Kakao.yang found in two different locations in Bali, in the village of Kaja Buahan District of Payangan, Gianyar and the Village of Tua, Marga, Tabanan regency subdistricts. Research carried out in the field with the exploration methods, isolation, identification and diversity analysis conducted at the Laboratory of Plant Taxonomy (Mycology), Department of Biology, Faculty of Mathematics, University of Udayana. Laboratory research conducted by isolating the roots, leaves, plant stems and content of the soil (rhizosphere) cocoa. Once isolated, grown on PDA medium subsequently incubated at room temperature 250C. Isolates that grow back isolated and purified on a PDA medium for further identified to the genera or species level. A total of six isolates of endophytic fungi identified in the rhizosphere and cocoa plant that is where four of these isolates were identified to species, two isolates were not identified until genus. Fungi were identified namely Aspergillus flavus, Rhizopus stolonifer, Cladosporium sphaeropermum, Trichoderma viride, isolates 1 and 2 isolates. Keywords: cocoa, endophytic fungi, highlands and lowlands